Book recommendation: Quality management system and business - Spasojević-Brkić, Vesna K; Milanovic, Dragan D; Knezevic, Snezana; Lazic, Danijela; Milanovic, Tanja (Journal of Applied Engineering Science, 2011)
BOOK RECOMMENDATION QUALITY MANAGEMENT SYSTEM AND BUSINESS PERFORMANCES By  V. Spasojević Brkić, D. Milanović, S. Knežević, D. Lazić and T. Milanović
Keywords: quality management system; Quality management; management systems; books